Community lung health service design for COPD patients in China by the Breathe Well group. - Pang H; Pan Z; Adams R; Duncan E; Chi C; Kong X; Adab P; Cheng KK; Cooper BG; Correia-de-Sousa J; Dickens AP; Enocson A; et al. (NPJ Prim Care Respir Med. 2022 Aug 19;32(1):27., 2022)
COPD is increasingly common in China but is poorly understood by patients, medications are not used as prescribed and there is no access to recommended non-pharmacological treatment. We explored COPD patients' and general practitioners' (GPs) knowledge of COPD, views on its management and the acceptability of a flexible lung health service (LHS) offering health education, exercise, self-management, smoking cessation and mental health support. Using a convergent mixed methods design, data were collected from patients and GPs using focus groups (FGs) in four Chinese cities, questionnaires were also used to collect data from patients. FGs were audio-recorded and transcribed. Quantitative data were analysed descriptively, thematic framework analysis was used for the qualitative data. Two-hundred fifty-one patients completed the questionnaire; 39 patients and 30 GPs participated in ten separate FGs. Three overarching themes were identified: patients' lack of knowledge/understanding of COPD, current management of COPD not meeting patients' needs and LHS design, which was well received by patients and GPs. Participants wanted COPD education, TaiChi, psychological support and WeChat for social support. 39% of survey responders did not know what to do when their breathing worsened and 24% did not know how to use their inhalers. 36% of survey respondents requested guided relaxation. Overall, participants did not fully understand the implications of COPD and current treatment was sub-optimal. There was support for developing a culturally appropriate intervention meeting Chinese patients' needs, health beliefs, and local healthcare delivery. Further research should explore the feasibility of such a service.
Keywords: Rehabilitation; Chronic obstructive pulmonary disease